2018
DOI: 10.5999/aps.2016.01718
|View full text |Cite
|
Sign up to set email alerts
|

Case of late hematoma after breast augmentation

Abstract: We present a case report of a patient who experienced a late, spontaneous breast hematoma 26 years after primary breast augmentation. Late hematomas are a rare complication of breast augmentation with uncertain etiology. In this case, there was no trauma, calcifications, or implant rupture. We believe the patient’s hematoma was secondary to erosion of a capsular vessel due to capsular contracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…This comparison of late breast hematomas with chronic subdural hematomas was described by Roman [23] in 2005 even. In the past year, 2018, two cases of late hematoma were reported: Kim et al [31] explained its development as a consequence of severe capsular contracture, while Dean et al [32] described a case of silicone extravasation that may have led to chronic lymphocytic granulomatous reaction and a consequent recurrent acute-on-chronic hematoma. Grippaudo et al [3] in 2013 reported a singular case of late hematoma developed 2 years after breast surgery, due to mechanical friction in the space between the two layers of a double capsule.…”
Section: Discussionmentioning
confidence: 99%
“…This comparison of late breast hematomas with chronic subdural hematomas was described by Roman [23] in 2005 even. In the past year, 2018, two cases of late hematoma were reported: Kim et al [31] explained its development as a consequence of severe capsular contracture, while Dean et al [32] described a case of silicone extravasation that may have led to chronic lymphocytic granulomatous reaction and a consequent recurrent acute-on-chronic hematoma. Grippaudo et al [3] in 2013 reported a singular case of late hematoma developed 2 years after breast surgery, due to mechanical friction in the space between the two layers of a double capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoma or increase in residual blood in the pocket represents a powerful medium for bacterial growth and also have been shown to carry a very high concentration of proinflammatory cytokines. 41 This could occur acutely from surgical dissection or in rare cases after erosion of vessels in the capsule. 41,42 Accordingly, clinical observations reveal a link between hematoma and capsular contracture formation.…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…41 This could occur acutely from surgical dissection or in rare cases after erosion of vessels in the capsule. 41,42 Accordingly, clinical observations reveal a link between hematoma and capsular contracture formation. 42 Furthermore, seroma and pocket infection likewise increase the risk of capsular contracture via a similar mechanism.…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…Written informed consent was obtained from all the patients prior A B 6) in 1992, late hematoma development around a breast implant has been described in the literature, which has been observed after reconstructive and aesthetic breast surgery with implants. The delayed post implantation breast hematoma mechanism is not yet well established (7), although previous authors correlated it with direct trauma, clotting disorders, and corticosteroid (8). Capsular contracture, the most common breast implantation complication, has been associated indirectly with late hematoma.…”
Section: Casementioning
confidence: 99%